Quantifying sustainability and resilience in food systems: a systematic analysis for evaluating the convergence of current methodologies and metrics - Hassan, Rasha; Di Martino, Marcello; Daher, Bassel (Frontiers in Sustainable Food Systems, 2025)
The global food system faces multiple challenges including growing demand, climate change, conflicts, economic shocks, pandemics, and disasters. Food systems aim to provide healthy and nutritious food for all, while minimizing environmental impacts, ensuring social equity and economic viability, and enhancing resilience to shocks and stresses. The fragility of the global food system has been exposed by COVID-19 and the Russia-Ukraine war, resulting in disruptions in supply chains and reduced access to food for vulnerable populations. Recognizing the importance of transitioning to more “sustainable” and “resilient” food systems, a notable gap exists in clear metrics for quantifying “sustainability” and “resilience,” hindering the ability to track progress and inform evidence-based decision-making. This paper explores the alignment of definitions and evaluation methods for “sustainability” and “resilience” in food systems literature, the diversity of existing metrics across regions and scales, and the distribution and distinctive characteristics of case studies that have implemented these quantification approaches. The analysis of the literature highlights a lack of consensus in defining food systems sustainability and resilience, highlighting the need for stakeholder- informed, context-specific metrics. The divergence observed in conceptualizations and methodologies illustrates challenges in achieving a unified assessment framework and bridging the gap between definitions and practical implementation. To address this, we propose the co-creation of practical, interpretable metrics tailored through stakeholder engagement, acknowledging the limitations of a one-size-fits-all approach. Notably, Life Cycle Assessment (LCA) and the Food-Energy-Water Nexus (FEWN) emerge as promising methodologies for comprehensively evaluating sustainability and resilience dimensions. This review underscores the importance of further conceptual and methodological refinement, alongside fostering regional and international collaboration, to advance the discourse and evidence-based action on sustainable and resilient food systems.